Things with wings - Avery, Dorothy; Cooper, Jennifer; Shortland Publications (Shortland Publications Auckland, N.Z, 1998)
Introduces children to various creatures capable of flight, enhancing their understanding of the animal kingdom through engaging illustrations and informative text.
Paperback edition with vibrant colour illustrations. Features a variety of flying creatures including birds, insects, mammals, reptiles, and fish. Designed for guided reading and writing; suitable for independent reading and writing.
For children aged 4 to 11 years.
Keywords: Flight (Animal locomotion), Animals, Picture books for children